2017
DOI: 10.24002/jik.v13i2.682
|View full text |Cite
|
Sign up to set email alerts
|

Mempertanyakan Privasi di Era Selebgram: Masih Adakah?

Abstract: Media baru semakin mempermudah manusia untuk berkomunikasi satu dengan yang lain, terutama dalam hal pencarian informasi. Media baru muncul akibat inovasi teknologi dalam bidang media yang meliputi televisi kabel, satelit, teknologi fiber optic, dan komputer (Croteau, 1997, h. 12). Media baru memberikan penjelasan mengenai dua perbedaan pandangan antara the first media age dan the second media age. The first media

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 0 publications
0
4
0
1
Order By: Relevance
“…The new media connected to the internet is digital media, which provides a new concept of understanding information and communication technology (ICT) media. The digitalization media that is currently popular with individuals is social media, which has become a new medium of interaction that creates space for people to update their status, write walls on social media (Facebook and WhatsApp), make tweets on social media (X), and change their profiles with various kinds of photos or videos on social media (Instagram, YouTube, or TikTok), which displays their existence [1], [2], [3].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The new media connected to the internet is digital media, which provides a new concept of understanding information and communication technology (ICT) media. The digitalization media that is currently popular with individuals is social media, which has become a new medium of interaction that creates space for people to update their status, write walls on social media (Facebook and WhatsApp), make tweets on social media (X), and change their profiles with various kinds of photos or videos on social media (Instagram, YouTube, or TikTok), which displays their existence [1], [2], [3].…”
Section: Introductionmentioning
confidence: 99%
“…In practice, parents ignore the requirements that need to be agreed to, including those related to children's privacy [5], [6], [11]. Uploaded photos or videos constitute privacy that must be carefully guarded, closed tightly, and not shared with other people to avoid misuse of information as a form of online crime [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Krisnawati revealed that privacy is an abstract concept that contains many meanings. This privacy refers to the word privacy in English which means a condition free from interference by others [4]. Referring to this meaning of privacy, each individual certainly has limitations about which ones can be disturbed and which cannot be disturbed by other individuals.…”
Section: Introductionmentioning
confidence: 99%
“…Penggunaan Instagram dan Youtube oleh public figure, disadari atau tidak, memengaruhi pengikutnya. Keduanya dianggap media yang terbuka bagi siapapun untuk mengekspresikan diri di ruang publik, yang kemudian dapat mempengaruhi persepsi masyarakat (Krisnawati 2017).…”
unclassified